Building intelligent interactive tutors : student-centered strategies for revolutionizing e-learning - Woolf, Beverly Park (Morgan Kaufmann Publishers/Elsevier, 2009)
Computers have transformed every facet of our culture, most dramatically communication, transportation, finance, science, and the economy. Yet their impact has not been generally felt in education due to lack of hardware, teacher training, and sophisticated software. Another reason is that current instructional software is neither truly responsive to student needs nor flexible enough to emulate teaching. The more instructional software can reason about its own teaching process, know what it is teaching, and which method to use for teaching, the greater is its impact on education.